2016
DOI: 10.1177/1475090216642466
|View full text |Cite
|
Sign up to set email alerts
|

Optimization design of tuned mass damper for vibration suppression of a barge-type offshore floating wind turbine

Abstract: An efficient method for restraining the large vibration displacements and loads of offshore floating wind turbines under harsh marine environment is proposed by putting tuned mass dampers in the cabin. A dynamics model for a barge-type offshore floating wind turbine with a fore-aft tuned mass damper is established based on Lagrange's equations; the nonlinear least squares Levenberg-Marquardt algorithm is employed to identify the parameters of the wind turbine; different parameter optimization methods are adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Previous research conducted by Adam and Furtmüller pointed out that a range of mass ratios of 2% to 8% are considered to be the practically applicable range for structural control . In addition, He et al concluded that the suppression rates of the vibration response for OWTs vary according to the TMD mass from 0.5% to 2% of the entire mass (tower‐RNA structure). Si et al evaluated the effectiveness of a TMD at reducing damage equivalent loads for a spar type OWT, with a TMD that accounts for 3.3% of the entire mass.…”
Section: Modeling Of Tmds In Fastv8mentioning
confidence: 99%
“…Previous research conducted by Adam and Furtmüller pointed out that a range of mass ratios of 2% to 8% are considered to be the practically applicable range for structural control . In addition, He et al concluded that the suppression rates of the vibration response for OWTs vary according to the TMD mass from 0.5% to 2% of the entire mass (tower‐RNA structure). Si et al evaluated the effectiveness of a TMD at reducing damage equivalent loads for a spar type OWT, with a TMD that accounts for 3.3% of the entire mass.…”
Section: Modeling Of Tmds In Fastv8mentioning
confidence: 99%
“…Similar numerical and experimental studies for FOWTs with the spar-type platforms have been proposed and carried out throughout the year [13][14][15]. Another possible candidate for the FOWT support platform is the distributed-buoyancy stabilization (barge) [16][17][18]. It achieves excellent stability with a high-water plane area, and its mooring system is primarily for station keeping and not for supplying the system stiffness.…”
Section: Introductionmentioning
confidence: 98%
“…Usually, the structural stabilization systems are either mounted on or embedded inside the main structure. This type of Tuned Mass Dampers (TMD) are designed to mechanically damp the vibration either passively, actively or even semi-actively [14][15][16][17]. The efficiency of these systems is associated with their mass, stiffness and damping coefficient.…”
Section: Introductionmentioning
confidence: 99%